Pharmacokinetics, Bioavailability, Excretion and Metabolism Studies of Akebia Saponin D in Rats: Causes of the Ultra-Low Oral Bioavailability and Metabolic Pathway - Pengfei Li; Jun Peng; Yuexin Li; Lili Gong; Yali Lv; He Liu; Tianhong Zhang; Song Yang; Hongchuan Liu; Jinglai Li; Lihong Liu (Frontiers Media S.A., 2021)
Background: Akebia saponin D (ASD) has a variety of biological activities and great medicinal potential, but its oral bioavailability is so low as to limit its development. Its pharmacokinetic profiles and excretion and metabolism in vivo have not been fully elucidated. This study was an attempt in this area.Methods: A simple LC-MS/MS method to simultaneously quantify ASD and its metabolites M1∼M5 in rat plasma, feces, urine and bile was established with a negative ESI model using dexketoprofen as the internal standard. Meanwhile, the UPLC-HR/MS system was used to screen all possible metabolites in the urine, feces and bile of rats, as compared with blank samples collected before administration. Absolute quantitative analysis was for M0, M3, M4, and M5, while semi-quantitative analysis was for M1, M2, and Orbitrap data.Results: The AUC0-t values after intravenous administration of 10 mg/kg and intragastrical administration of 100 mg/kg ASD were 19.05 ± 8.64 and 0.047 ± 0.030 h*μg/ml respectively. The oral bioavailability was determined to be extremely low (0.025%) in rats. The exposure of M4 and M5 in the oral group was higher than that of M0 in the terminal phase of the plasma concentration time profile, and ASD was stable in the liver microsome incubation system of rats, but metabolism was relatively rapid during anaerobic incubation of intestinal contents of rats, suggesting that the low bioavailability of ASD might have been attributed to the poor gastrointestinal permeability and extensive pre-absorption degradation rather than to the potent first pass metabolism. This assertion was further verified by a series of intervention studies, where improvement of lipid solubility and intestinal permeability as well as inhibition of intestinal flora increased the relative bioavailability to different extents without being changed by P-gp inhibition. After intravenous administration, the cumulative excretion rates of ASD in the urine and bile were 14.79 ± 1.87%, and 21.76 ± 17.61% respectively, but only 0.011% in feces, suggesting that the urine and bile were the main excretion pathways and that there was a large amount of biotransformation in the gastrointestinal tract. Fifteen possible metabolites were observed in the urine, feces and bile. The main metabolites were ASD deglycosylation, demethylation, dehydroxylation, decarbonylation, decarboxylation, hydroxylation, hydroxymethylation, hydroxyethylation and hydrolysis.Conclusion: The pharmacokinetics, bioavailability, metabolism and excretion of ASD in rats were systematically evaluated for the first time in this study. It has been confirmed that the ultra-low oral bioavailability is due to poor gastrointestinal permeability, extensive pre-absorption degradation and biotransformation. ASD after iv administration is not only excreted by the urine and bile, but possibly undergoes complex metabolic elimination.